Evaluation of Surgical Treatment and the Relationship between Thoracolumbar Injury Severity and Classification Score and Preoperative Cross-Sectional Area in Patients with Thoracolumbar and Lumbar Burst Fractures - Azimi, Parisa; Azhari, Shirzad; C. Benzel, Edward; Sadeghi, Sohrab; Nayeb Aghaei, Hossein; Mohammadi, Hassan Reza; Khayat Kashani, Hamid Reza; Matin-rohani, Shervin (International Clinical Neuroscience Journal, 2017)
Background: The aim of the study was to establish a correlation between (1) the Thoracolumbar Injury Severity and Classification score (TLICS) and sensory scores and motors scores of the American Spinal Injury Association (ASIA) Scale (surgical outcome); correlation between preoperative cross-sectional area (CSA) and the ASIA; (2) to establish a correlation between the TLICS and the CSA in thoracolumbar and lumbar burst fracture (TLBF) patients and (3) the evaluation of surgical outcome based on the ASIA scale and its relationship to TLICS. Methods: This was a prospective study and 67 patients (mean age 30.3 ± 8.1 years; 18.2% were female) were assessed. The TLICS was determined and TLICS > 4 was hypothesized to be consistent with an indication for surgery. Nerve injury was assessed according to ASIA. The CSA and the ASIA were measured at two points in time: pre- and postoperative assessments. The surgical outcome and correlations were assessed. Results: Patients were followed an average of 26.2 months. ASIA sensory scores and motor scores were improved significantly at last follow-up. No patient experienced neurological worsening during follow-up. No significant correlations were observed between the ASIA and the CSA at either the pre- or postoperative periods. However, there was a statistically significant correlation between TLICS and the ASIA motor and ASIA sensory (P < 0.01 and P < 0.02 respectively). Conclusion: The findings confirm that a TLICS > 4 may be applied in the decision-making process for surgery for TLBF. However, the CSA is not useful for decision making for this pathology.